Hubungan Antara Konsep Diri Dengan Disiplin Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas VIII SMP N 3Tigo Nagari Kabupaten Pasaman. - Yulianti, Susi; Isnaniah, Isnaniah; Aniswita, Aniswita; Rahmat, Tasnim (Kadikma, 2024)
The background of the problem is the lack of self-concept and discipline of student learning. The purpose of this study is to find out if there is a significant relationship between self-concept and student learning discipline in math subjects in class VIII of SMPN 3 Tigo Nagari, Pasaman Regency Year lesson 2022/20233. This type of research is the study of correlation with quantitative methods. Research results show that students' self-concept and discipline in mathematics subjects are correlated by 0.612 with strong categories, processed using a real-time t-test α=0.05, thus obtaining a t_count>t_table value of 4.092>1.701 and from the calculation of SPSS software sig = 0.000<0.05 so H_0 is rejected and H_a is accepted. So, it can be concluded that there is a significant relationship between self-concept and student learning discipline in math subjects in class VIII of SMPN 3 Tigo Nagari, Pasaman Regency in the 2022/2023 Academic Year. Keyword : Relationship, Self-concept, Student Learning Discipline